Los conectores pragmáticos en el habla culta costarricense - Solano Rojas, Yamilet (Revista de Filología y Lingüística de la Universidad de Costa Rica, 2015)
Expressions such as bueno, idiay, verdad, digamos.fijáte, etc., which reccurvery frequendy in spoken Costa Rican Spanish, traditionalIy have been stigrnatized as pet words without much meaning or function. On the basis of data from recorded interviews, cooversations and lectures, the author of the artic1e posits that they are pragmatic connectors with important phatic and discourse organizing functions which make them necessary and even obligatory in spontaneous speech. This explains why alI speakers, inc1uding those aware of the fact that they are coosidered "errors", keep using them.